About probability of error detection of unauthorized impacts on pipeline with active vibroacoustic method of control - A. A. Fedotov; Yu. G. Malinovskiy (Омский научный вестник)
The scientific community has developed many ways to ensure the safety of transportation of petroleum products by automated means. An urgent task is to increase the efficiency of identifying the type of unauthorized impact on the pipeline and assess the errors probabilities in the detection of violations. The paper presents the results of an experimental assessment of the probabilistic characteristics of the detector based on the previously proposed active vibro-acoustic method of control. The values of informative features in vibroacoustic signals are obtained depending on the size of the local heterogeneity and the signal-to-noise ratio. The probability of recognition error and the required number of accumulated signals for system operation in the far zone are determined. The conclusion is made about the consistency of the proposed algorithm for identifying the type of unauthorized exposure.